Learning English Through Translating Activity: A Vocational High School Students' Reflection - Nabila Auliarahma (La Tansa Mashiro, 2020)
The use of translating activity as a means of language learning as well as a teaching method has received different compliments and criticism throughout English as Foreign Language (EFL) long history. Even though translating activity has been less preferred by teachers and educators, most students, on the other hand, are believed to frequently use translation to help them to learn certain language. This descriptive qualitative study attempts to discover Vocational High School (VHS) students’ reflection on the helpfulness of translating activity as a means of language learning. 38 VHS students of 10th grade were asked about their general opinion on translating activity, instructed to keep a learning diary throughout the English course, and lastly a small representing amount of them were chosen to be interviewed. All of these procedures were done to help the researcher gain insight from the students’ viewpoint about their reflection on the entirety of translating activity and how it affects their language learning process. At the end of the research, it is found that according to the students translating activity is indeed very helpful for them to learn EFL, especially with the role of technology that contributes to the improvement of translating activity; diminishing its ineffective and time-consuming nature. Therefore, this study can be considered to provide the readers with insight regarding students’ reflection on translating activity and their implications for students’ language learning process.